Handbook of research on wireless multimedia quality of service and solutions - Cranley, Nicola; Murphy, Liam (Information Science Reference, 2009)
"This book highlights and discusses the underlying QoS issues that arise in the delivery of real-time multimedia services over wireless networks"--Provided by publisher